ASSOCIATION OF ADIPOSITY, TELOMERE LENGTH AND AGE: NHANES 1999–2002 - Batsis, J.A. (Innov Aging, 2017)
Background: Telomere shortening is associated with age and risk of medical co-morbidity. We assessed the relationship between measures of adiposity with leukocyte telomere length and whether it is influenced by age. Methods:Subjects with dual energy x-ray absorptiometry (DEXA) measures were identified using the National Health and Nutrition Examination Survey 1999–2002. Obesity was categorized using body fat (BF%: low/high; men≥25%; females ≥35%), body mass index (BMI) categories, and waist circumference (WC) (low/high, men≥102cm; females≥88cm). Telomere length relative to standard reference DNA (T/S ratio) was assessed using quantitative polymerase chain reaction. Weighted multivariable regression models evaluated the association of telomere length with adiposity, both continuously and categorically (low/normal BF%, low/high WC,BMI 18.5–24.9kg/m(2)=referent), adjusted for age (where indicated), race, sex, education, smoking, co-morbidities, and physical activity. The interaction between age strata and adiposity was assessed and subsequent models stratified by age. Results: We identified 7,827 subjects (4,056 female; 2672 age≥60years). Mean age was 46.1 years. Overall telomere length was 1.05 ± 0.01 (SE) that differed by BF% (low/high: 1.12 ± 0.02 vs. 1.03 ± 0.02;p<0.001), BMI (underweight 1.08 ± 0.03; normal 1.09 ± 0.02; overweight 1.04 ± 0.02; obese 1.03 ± 0.02; p<0.001), and WC (low/high 1.09 ± 0.02 vs. 1.02 ± 0.02; p<0.001). Adjusted estimates between telomere length and adiposity measures were: BF% (β=-0.0033 ± 0.0008;p<0.001), BMI (β=-0.025 ± 0.0008;p=0.005), and WC (β=-0.0011 ± 0.0004;p=0.007). All age x adiposity interactions were significant (p<0.001). Model estimated mean difference (Age>60–Age<60) was: BF% (-0.14 ± 0.01;p<0.001), BMI (-0.15 ± 0.001;p<0.001), and WC (-0.0015 ± 0.0004;p<0.001). No significant association was present between telomere length and adiposity over age≥60. Conclusions: A negative association between adiposity and telomere length was observed but age abrogates this relationship.